A ½ spin fiber model for the electron - Markoulakis, Emmanouil; Antonidakis, Emmanuel (International Journal of Physical Research, 2022)
The Standard Model and Quantum Mechanics studies the quantum world as a collection of probabilistically interacting particles and does not tell us what a single isolated particle like the electron is, thus its intrinsic detailed field mechanics and how these are generating its intrinsic property values like charge, spin, magnetic moment and handedness. We herein are translating these intrinsic physical properties of the electron to a novel 4-dimensional (i.e. three spatial plus one temporal) fiber spinor and showing their possible deeper correlation and interconnection combined under a single energy manifold. From physical quantum emulation observations, mathematical analysis and Wolfram Alpha parametric polar simulations and mathematical 4D animations we calculated a fiber model for the dressed bare mass electromagnetic field of the electron that results to all of its known measured intrinsic properties. Therefore our model is an intrinsic mechanics model for the electron at rest and shows the possibility that the elementary electron although it has no inner sub-particles, it can posses a specific energy flux manifold. Why an electron is actually a Â½ spin geometry, twisted photon. The fine structure constant is explained as a topological feature, proportionality constant, embedded inside our proposed fiber model for the electron. Our novel fiber model opens up a new door on theoretical intrinsic mechanics physics of elementary particles beyond the Standard Model.Â